Integrating Problem Structuring Methods And Concept-Knowledge Theory For An Advanced Policy Design: Lessons From A Case Study In Cyprus. Issue 6 (1st November 2020) - Pluchinotta, Irene; Giordano, Raffaele; Zikos, Dimitrios; Krueger, Tobias; Tsoukiàs, Alexis
Abstract: Evidence suggests that policies frequently fail due, on the one side, to a simplification of the uncertainty and complexity associated with stakeholders' problem-understanding and, on the other side, due to the lack of methodologies for innovative generation of policy alternatives. This work describes a methodology based on the integration of Problem Structuring Methods and Concept-Knowledge Theory as a mean to transform ambiguity in problem-framing from a barrier to an enabling factor in collaborative settings. This methodology supports the generative design process for innovative and consensual policies. The methodology was implemented for a case of designing water management policy in the Republic of Cyprus.